The Writing Workshop - Its support, practice, and value - Godinez-Ortega, Christine (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
This short paper delivered as a keynote speech tackles the value and popularity of writing workshops. It gives a historical perspective on the support, practice and value of writing and writers workshops. It defines historical fiction and challenges academic institutions especially, to look upon historical fiction as a way of understanding the present.